Comparative Study on Multi-Joint and Single-Joint Exercises in Bodybuilding Economics - Geanta, Vlad Adrian; Herlo , Julien Narcis (Arena-Journal of Physical Activities, 2021)
Introduction. A relevant aspect of bodybuilding is that each person wants to improve muscle mass, or remove adipose tissue and build muscle, but this can only be done through a specific training program. The purpose of this current research is to make a comparative study between MJ and SJ exercises, and to see if through specific training routines, the subjects can achieve the proposed objectives, muscular hypertrophy or weight loss. Methods. The study was carried out on a number of 30 subjects divided in two groups with specific trainings methods. To obtain specific results, we will develop 2 training routines, one routine for hypertrophy based on multi-joint exercises, and one for weight loss based on single-joint exercises. These training structures will be consistent with the specific objectives, in terms of load used, number of repetitions and rest break. Results. Following the experiment, we recorded a series of significant results, regarding the HMM group, respectively the DM group. The most representative increases were recorded in the chest muscle from HMM group, with an increase of 5.86%. The smallest increase was on the chest on DM group, -2.57%, and in the thighs the highest of -4.15%. Conclusions. The hypothesis works to confirm, this allows us to affirm that it is possible as through a predetermined program with multi-joint exercises, and a program with single-joint exercises combined with cardio routines, subjects accumulate muscle mass, or lose weight by reducing the perimeters of body segments, to reach the desired physical shape.